The role of proteolysis in cell cycle progression in Schizosaccharomyces pombe. - Yamano, H (1996)
A cell-free system derived from Xenopus eggs was used to identify the 'destruction box' of the Schizosaccharomyces pombe B-type cyclin, Cdc13, as residues 59-67: RHALDDVSN. Expression of indestructible Cdc13 from a regulated promoter in S.pombe blocked cells in anaphase and inhibited septation, showing that destruction of Cdc13 is necessary for exit from mitosis, but not for sister chromatid separation. In contrast, strong expression of a polypeptide comprising the N-terminal 70 residues of Cdc13, which acts as a competitive inhibitor of destruction box-mediated proteolysis, inhibited both sister chromatid separation and the destruction of Cdc13, whereas an equivalent construct with a mutated destruction box did not. Appropriately timed expression of this N-terminal fragment of Cdc13 overcame the G1 arrest seen in cdc10 mutant strains, suggesting that proteins required for the initiation of S phase are subject to destruction by the same proteolytic machinery as cyclin.